Origin of natural gas within the deep-sea uncompacted sediments of the Shenhu area, northern South China Sea: Geochemical and methanogenic cultivation results. (January 2023) - Lai, Hongfei; Deng, Yinan; Yang, Lu; Liang, Jinqiang; Dai, Lirong; Li, Ling; Fang, Yunxin; Liu, Laiyan; Kuang, Zenggui
Abstract: Large amounts of natural gas are dispersed at low concentrations or have accumulated to form highly saturated gas hydrates within uncompacted deep-sea (water depth usually >500 m) sediments worldwide. However, studies on their origin and microbial genetic mechanism are scarce. Using the gas hydrate prolific region of the Shenhu area in the northern South China Sea as our study area, we systematically investigated the genetic types and generation pathways of the natural gas in those sediments based on gas geochemical and anaerobic methanogenic cultivation results. Our results indicated that natural gas within the uncompacted deep-sea sediments in the Shenhu area is dominated by microbial methane (>95%) with a minor amount of biodegraded hydrocarbon (ethane to propane) (<1%). The microbial methane within the highly saturated gas hydrate reservoir was produced by hydrogenotrophic methanogens in the deeper buried optical methanogenic zone (25 °C < in-situ temperature <85 °C), rather than in the in-situ gas hydrate layer. However, the primary microbial gas generative potential of the upper part of the methanogenic zone (28–300 mbsf) in the Shenhu area is relatively poor because of insufficient methanogenic substrates. These findings suggest a strong vertical heterogeneity of methanogenesis potential in the methanogenic zone in the Shenhu area, which may be a common phenomenon in the worldwide marine sediment environments, especially in the regions with relatively low organic matter richness. Highlights: Strong vertical heterogeneity of methanogenesis potential is existed within the methanogenic zone of marineenvironments. The poor primary microbial gas generative potential in Shenhu area is attributed to insufficient methanogenic substrates. The microbial methane withingas hydrates in Shenhu area were generated in the lower part of methanogenic zone. The microbial methane withingas hydrates in the Shenhu area mainly produced via hydrogenotrophic methanogenetic pathways.